Shifting to Online Mode: Analyzing Parents’ Perceptions of Social Distancing and its Effects on Academic and Social Learning of Primary School Students - Ali, Saqib; Uzair ul Hassan, Muhammad; Parveen, Iram (PJDOL, 2024)
This study investigated the effect of social distancing on academic and social learning of primary school students during pandemic in Pakistan. For this research study, a mixed-methods convergent parallel research design was employed. Through a questionnaire, quantitative responses were collected from 120 parents whereas for qualitative responses, face-to-face interviews were conducted with twenty parents. Descriptive and inferential statistics were applied to analyze the quantitative data, whereas thematic analysis was used for analyzing qualitative data. According to the study results, parents perceived that social distancing affected the academic and social learning of their children during the pandemic in the shifted phase from offline to online mode, although there were variations with respect to the demographics selected for this study. Based on the parents’ interviews, the majority agreed that social distancing had a negative effect on children’s academic and social learning, in addition to tempering their communication skills and disrupting the psychological health, which consequently generated a learning gap. It is recommended that the concerned authorities may take such initiatives to address and mend the learning loss of children relevant to their academic and social skills in the post-pandemic era.